Combination of transsphenoidal endoscopic surgery and presurgical somatostatin analogs in thyrotropin (TSH)-secreting pituitary adenomas: Treatment outcome and long-term remission at a single pituitary center - Liu, Jie; Yang, Yamei; Duan, Lian; Chai, Xiaofeng; Zhu, Huijuan; Deng, Kan; Lian, Xiaolan; Yao, Yong (Frontiers in Endocrinology, 2022)
Background Thyrotropin (TSH)-secreting pituitary adenomas (TSHomas) account for an extremely rare group of pituitary adenomas. Few studies examined the sensitivity and efficacy of presurgical somatostatin analogs (SSAs) and described the long-term remission under such treatment modality. The aim of the present study was to assess the efficacy of presurgical SSA treatment and long-term remission after surgery. Methods A retrospective cohort of 65 TSHoma patients who received endoscopic transsphenoidal pituitary surgery between 2011 and 2020 in a single pituitary center in China was established. Data were analyzed for sex differences and different types of SSA and ultimately to explore the hormonal cutoff for remission prediction. Results TSHomas had a predominant female preference in this cohort (43 women vs. 22 men). Baseline FT3 was higher in men [7.543 ± 2.407 vs. 5.58 (4.99, 6.58), p = 0.019], which was consistent with its longer diagnosis time and larger tumor volume. The median medication time for hormonal control was 2. 5 days for short-acting SSA and 4. 0 weeks for long-term SSA. Patients with long-acting SSA had a shrinking maximum tumor diameter at a median of 1.0 (−1.6, 4.925) mm. Only 10 patients (15.38%) were not in complete remission among whom 8 patients were not en-bloc resected and 2 patients had tumor recurrence after 81.6 and 10. 7 months of complete removal. Postsurgical thyroid hormones (within 1 week) of TSH <0.094 μIU/ml were identified as the cutoff for remission using the ROC curve. Conclusions The combination of endoscopic transsphenoidal surgery and presurgical SSA TSHomas provided a higher long-term remission for TSHomas.